2009
DOI: 10.1177/0165025409103871
|View full text |Cite
|
Sign up to set email alerts
|

Categorization of regional and foreign accent in 5- to 7-year-old British children

Abstract: This study examines children's ability to detect accent-related information in connected speech. British English children aged 5 and 7 years old were asked to discriminate between their home accent from an Irish accent or a French accent in a sentence categorization task. Using a preliminary accent rating task with adult listeners, it was first verified that the level of accentedness was similar across the two unfamiliar accents. Results showed that whereas the younger children group behaved just above chance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
132
4
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(154 citation statements)
references
References 39 publications
15
132
4
3
Order By: Relevance
“…This account of course presumes that young children can detect (explicitly or implicitly) that a speaker has an accent, a task that other studies suggest is difficult for 5-year-olds (Floccia, Butler, Girard, & Goslin, 2009;Girard, Floccia, & Goslin, 2008;Wagner, Clopper, & Pate, 2014; though see Kinzler, Dupoux, & Spelke, 2007, for a different account).…”
Section: Discussionmentioning
confidence: 97%
“…This account of course presumes that young children can detect (explicitly or implicitly) that a speaker has an accent, a task that other studies suggest is difficult for 5-year-olds (Floccia, Butler, Girard, & Goslin, 2009;Girard, Floccia, & Goslin, 2008;Wagner, Clopper, & Pate, 2014; though see Kinzler, Dupoux, & Spelke, 2007, for a different account).…”
Section: Discussionmentioning
confidence: 97%
“…One explanation for these findings is that at least initially, children's representations are organized along a quantitatively defined continuum, anchored by their "home" accent, which forms the core set of their experiences, with regional accents treated as intermediate between the home and foreign accent (Wagner et al, 2014). With more experience, older children are able to reliably distinguish their own from another unfamiliar regional variety (Floccia et al, 2009) and make judgements in line with general social stereotypes. For example, children aged 9-10 years in Illinois and Tennessee, USA, judged northern-accented American English speakers to be more intelligent than those with southern-accented American English (Kinzler & DeJesus, 2013).…”
Section: Accent Variation Categorization and The Role Of Experiencementioning
confidence: 99%
“…Few studies have investigated this question, and the results are mixed. For example, Jeffries (2016) found that monolingual English children aged 3-4 years, growing up in Yorkshire but with a parent from outside Yorkshire (i.e., who spoke with a different accent from that of the community), were better able to group talkers according to ac-cent when the target variables contained different rather than the same phonemes (see also Floccia et al, 2009). Interestingly, children with parents from outside Yorkshire were also better able to recognize a familiar talker (in this case, a familiar teacher) using phonetic accent features.…”
Section: Accent Variation Categorization and The Role Of Experiencementioning
confidence: 99%
See 2 more Smart Citations